Ethnomedicinal plants used for oral health care by the Yanadi tribe of Nellore district, Andhra Pradesh, India - Sarah Sheela Emerald (International Journal of Phytomedicine, 2019)
Yanadis are one of the under privileged scheduled tribes mainly lives in coastal part of Andhra Pradesh state which are living in isolation and are treated as lowest social group and placed just above the scheduled castes in social hierarchy in the Potti SriRamulu Nellore districts. Nellore district has the highest population of Yanadi in the state. Like any other tribe in the country Yanadi also depend on herbs, barks and roots for curative procedures and maintenance of health. Enhancing the sustainable use and conservation of indigenous knowledge of useful and medicinal plants may benefit and improve the living standards of poor people. The aim of this study is to document the ethno medicinal plants used for oral diseases using a specific questionnaire form the traditional healers, elderly people and residents of Gonepalli village of Nellore district. Information on 3 trees, 7 different herbs along with alum and camphor is documented along with the details of the parts of the plants used. This study concludes that this documentation will help to preserve the rich herbal treasure of our tribal population as well as help the pharmacists to derive the active compounds and incorporate them in modern medicine in future.